Compatibilization of polymer blends : micro and nano scale phase morphologies, interphase characterization, and properties - Thomas, Sabu; Ajitha, A. R. (Elsevier, 2020)
Compatibilization of Polymer Blends: Micro and Nano Scale Phase Morphologies, Interphase Characterization and Properties offers a comprehensive approach to the use of compatibilizers in polymer blends, examining both fundamental and advanced knowledge in the field. The book begins by introducing polymer blends, describing thermodynamics, miscibility, and phase separation, and explaining the main concepts of compatibilization. Other sections cover theoretical approaches for nearly compatible blends, incompatible blends, nanofillers, physical compatibilization, reactive compatibilization, morphological and structural characterization, and physico-mechanical characterization. Finally, key application areas are covered, including biomedical applications, packaging and automobile engineering. While this book will be a highly valuable reference source for academics, researchers and postgraduate students interested in polymer blends, it will also be ideal for anyone involved in the fields of polymer science, polymer chemistry, polymer physics, materials science, scientists, R & D professionals, and engineers in involved in the development or engineering of polymer products. Offers detailed and systematic coverage of essential and advanced topics relating to the compatibilization of polymer blends Presents a critical analysis of the effect of compatibilization on morphology and thermal, mechanical, electrical and viscoelastic properties of polymer blends Draws on novel studies and state-of-the-art research, discussing the latest issues and developments